The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.amepre.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Aged Adults' Sitting Time in Three Contexts

Abstract: Background: To develop evidence based approaches for reducing sedentary behavior, there is a need to identify the specific settings where prolonged sitting occurs, associated factors, and variations.Purpose: To examine the sociodemographic and health factors associated with mid-aged adults' sitting time in three contexts, and variations between week and weekend days.Methods: A mail survey was sent to 17,000 adults (aged 40-65 years) in 2007; 11,037 responses were received (68.5%); and 7,719 were analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 22 publications
6
33
1
2
Order By: Relevance
“…We have previously shown that lower SEP is linked consistently with increased TV viewing and other recreational screen time in Scottish adults,12 a finding that has been confirmed by studies in other countries such as Belgium,13 Australia14 15 and the USA16 that used TV as a proxy for ST. However, these findings are not necessarily generalisable to overall sedentary or sitting time because TV viewing is a complex exposure that seems to be a poor index of overall ST 17.…”
Section: Introductionmentioning
confidence: 54%
“…We have previously shown that lower SEP is linked consistently with increased TV viewing and other recreational screen time in Scottish adults,12 a finding that has been confirmed by studies in other countries such as Belgium,13 Australia14 15 and the USA16 that used TV as a proxy for ST. However, these findings are not necessarily generalisable to overall sedentary or sitting time because TV viewing is a complex exposure that seems to be a poor index of overall ST 17.…”
Section: Introductionmentioning
confidence: 54%
“…However, the findings that less healthy participants in our study were more sedentary and did less even light physical activity are largely consistent with studies focused on disease populations. Such studies have similarly found that less healthy participants spent less time doing chores and more time watching television than healthy counterparts [10,31].…”
Section: Key Findingsmentioning
confidence: 91%
“…Furthermore, while men generally do more physical activity than women [8], with increasing age (over 60 years) men become more sedentary while women maintain the same level of light physical activity [9]. The type of sedentary behaviour is also different between the sexes, with men sitting longer to watch television or use a computer while women sit longer to do hobbies or read [10]. Moreover, women are reported to sleep for a longer duration than men [11].…”
Section: Introductionmentioning
confidence: 99%
“…While device-based measurement is leading to significant progress, self-report methods nevertheless remain essential elements of population-prevalence studies; for example, using the iPAQ instrument, wide international variations in the prevalence of prolonged sitting have been identified . Context-specific studies using the appropriate self-report methods have not only added much-needed precision in reducing measurement error (Burton et al, 2012;Chau et al, 2011Chau et al, , 2012aClark et al, 2011b;Marshall et al, 2010;Oliver et al, 2010;Speck and Schmitz, 2011;van der Ploeg et al, 2010), but have also strengthened the basis for understanding how environmental attributes might influence sedentary behaviors (Bennie et al, 2011).…”
Section: Sedentary Behavior: Research Opportunitiesmentioning
confidence: 99%